The X-ray emission of the γ Cassiopeiae stars. Issue 5 (1st September 2016) - Smith, Myron A.; Lopes de Oliveira, R.; Motch, C.
Abstract: Long considered as the "odd man out" among X-ray emitting Be stars, γ Cas (B0.5e IV) is now recognized as the prototype of a class of stars that emit hard thermal X-rays. Our classification differs from the historical use of the term " γ Cas stars" defined from optical properties alone. The luminosity output of this class contributes significantly to the hard X-ray production of massive stars in the Galaxy. The γ Cas stars have light curves showing variability on a few broadly-defined timescales and spectra indicative of an optically thin plasma consisting of one or more hot thermal components. By now 9–13 Galactic ≈ B0-1.5e main sequence stars are judged to be members or candidate members of the γ Cas class. Conservative criteria for this designation are for a ≈ B0-1.5e III–V star to have an X-ray luminosity of 10 32 –10 33 ergs s −1, a hot thermal spectrum containing the short wavelength Ly α Fe XXV and Fe XXVI lines and the fluorescence FeK feature all in emission. If thermality cannot be demonstrated, for example from either the presence of these Ly α lines or curvature of the hard continuum of the spectrum of an X-ray active Be star, we call them γ Cas candidates. We discuss the history of the discovery of the complicated characteristics of the variability in the optical, UV, and X-ray domains, leading to suggestions for the physical cause of the production of hard X-rays. These include scenarios in which matter from the Be star accretes onto a degenerate secondary star and interactions between magnetic fields on the Be star and its decretion disk. The greatest aid to the choice of the causal mechanism is the temporal correlations of X-ray light curves and spectra with diagnostics in the optical and UV wavebands. We show why the magnetic star-disk interaction scenario is the most tenable explanation for the creation of hard X-rays on these stars.